2008
DOI: 10.1094/phyto-98-3-0270
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for Development of Powdery Mildew of Tomato Caused by Oidium neolycopersici

Abstract: Oidium neolycopersici causes severe powdery mildew on all aerial parts of tomato, excluding the fruit. The objective of the present work was to examine factors that influence the development of O. neolycopersici on tomato and to identify potential methods for managing tomato powdery mildew. Under controlled conditions, the highest rates of conidial germination were observed at 25 degrees C, 99% relative humidity (RH) and minimal light, and the lowest on leaves adjacent to fruits. Optimal conditions for appress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 28 publications
1
42
1
Order By: Relevance
“…Jacob et al (2008) found that the highest rates of conidial germination were observed at a minimum light intensity, optimal conditions for appressoria formation were at 1750 lx, and the greatest number of conidia was produced at the highest light intensity, 5150 lx. similar results were confirmed by Kashimoto et al (2003a), who found, that optimal light conditions for development of a Japanese isolate of O. neolycopersici were 3,500 lx (~62.2 μmol.m −2 .s −1 ), while in their experiments this intensity was the maximal tested, and under lower light intensity the rate of pathogen development was limited.…”
Section: Changes In Photosynthesis Of Host Plantsmentioning
confidence: 91%
See 3 more Smart Citations
“…Jacob et al (2008) found that the highest rates of conidial germination were observed at a minimum light intensity, optimal conditions for appressoria formation were at 1750 lx, and the greatest number of conidia was produced at the highest light intensity, 5150 lx. similar results were confirmed by Kashimoto et al (2003a), who found, that optimal light conditions for development of a Japanese isolate of O. neolycopersici were 3,500 lx (~62.2 μmol.m −2 .s −1 ), while in their experiments this intensity was the maximal tested, and under lower light intensity the rate of pathogen development was limited.…”
Section: Changes In Photosynthesis Of Host Plantsmentioning
confidence: 91%
“…All pictures taken 9 days after inoculation (Prokopová et al 2010) powdery mildews is significantly affected by host genotype and by combinations of environmental variables, including temperature, relative humidity and light. The basic conditions important for development of O. neolycopersici have also been studied (Fletcher et al 1988;Hannig 1996;Whipps and Budge 2000;Jacob et al 2008;Mieslerová and Lebeda 2010).…”
Section: Changes In Photosynthesis Of Host Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective control of powdery mildew can be achieved by applying fungicides at early stages of the disease development. (Jacob et al, 2008;Jones et al, 2001) spider Mite…”
Section: Powdery Mildewmentioning
confidence: 99%